Educational Inclusion through the Universal Design for Learning: Alternatives to Teacher Training - Diaz-Vega, Miriam; Moreno-Rodriguez, Ricardo; Lopez-Bastias, Jose Luis (Education sciences, 2020)
Universal design for instruction (UDI) is a teaching strategy that has proved its value in the process of educational inclusion, resulting in a fundamental tool for the achievement of objective 4 of the 2030 agenda for sustainable development. The lack of time of university professors and the scarce training offered in this subject make it difficult to know and implement UDI in university classrooms, increasing the risk of exclusion of students with some kind of disability. This study analyses the level of knowledge and implementation of the principles and strategies of UDI by university professors. Those professors did not have prior training, but they had access to the Curricular Adaptations of University Students with Special Educational Needs (CAUSSEN) tool as guide to implement different guidelines. The CAUSSEN tool is a document, developed by the Unit of Attention to People with Disability, in which there is information about UDI guidelines and accommodations referring to students with special educational needs. Results show a wide implementation of the UDI principles, despite the low level of previous knowledge its principles. This study concludes that there are practical alternatives to the lack of training, and that teachers’ self-perception of their own effectiveness and ability to cope with the inclusion of all students should be strengthened.